Praktik Pedidikan Karakter Religius dan Disiplin di SD Muhammadiyah Program Khusus Kottabarat Surakarta Tahun Pelajaran 2016/2017 - Sukasmin, Sukasmin; , Dr. Mohamad Ali. M.Pd (2016)
Character education try to apply every good usual to the students in order to act and have certain attitude based on the culture value and nation character. Religion value and discipline need to learning to students early because with the character education practice the student will rise their mind word and act. This research is call field research which use descriptive qualitative approuch with data source from headmaster, teachers, and the students also documents in Muhammadiyah Special Program Elementary School Kottabarat. The collecting data documentation. While the method that is used is inductive method. Result of this research in Muhammadiyah Special Program Elementary School Kottabarat, practice of character education in religious and disipline with integration way in school culture likes moslem dress, shake hands, be rid of the convering feet, stop activities when adzan's sound, fryday's give, look for clean, clean and neat dress based on the uniform, not to buy meal in the school, obligation prays and pray dhuha, the school use full day school system, character education practice in Muhammadiyah special program Elementary School Kottabarat pass through role, punishment, achivement, , customary, example and purpose.